PENGEMBANGAN POTENSI EKONOMI BIRU MELALUI PEMBANGUNAN TEMPAT PENDARATAN IKAN BAGI MASYARAKAT DUSUN SEPI, DESA BUWUN MAS, KECAMATAN SEKOTONG, KABUPATEN LOMBOK BARAT - Muliawan, Ahmat; Muslihah, Baiq Wanda Tika; Naora, Baiq Ananda Awalia; Salsabila, Nadina; Arisqi, Dimas; Aldian, Aldian; Fathin, Lalu Ridho Alif; Putri, Ariyanti Ultania; Larasati, Widistia Indah; Handini, Auliya Alfi (Universitas Mataram, 2024)
Kuliah Kerja Nyata (KKN) are a form of community service activities carried out by universities. In KKN activities carried out in Buwun Mas Village, Sekotong District, West Lombok Regency, a group of Mataram University students and lecturers carried out various activities with the main target of developing the potential of the blue economy. The aim of implementing this KKN activity is to answer various social issues found, including in terms of education, health and fisheries. Tempat Pendaratan Ikan (TPI) have an important role in the fisheries supply chain, functioning as landing, handling and distribution centers for marine catches. This research aims to analyze the function and sustainability of TPI in the Buwun Mas area and its impact on the local fishermen's economy. The research methods used include field surveys, interviews with fishermen, and analysis of secondary data related to fisheries production and local economic contribution. The research results show that well-managed TPI not only increases the quality and selling value of the catch, but also contributes significantly to increasing fishermen's income and local food security. However, challenges related to inadequate infrastructure and climate change impacting fishing patterns need to be addressed to ensure the sustainability of TPI in the future. Therefore, a more comprehensive management strategy and the application of environmentally friendly technology are needed to support the sustainability of the fisheries sector in Indonesia